An explanatory study on benefits of implementing progressive Wealth Tax in South Africa - Dudumashe, Thobela (University of the Witwatersrand, Johannesburg, 2023)
In the history of South Africa, there has been a growing imbalance between social behaviours and economic growth. Over the years, the government has promised to build a South Africa free of poverty, inequality, and unemployment. Low economic growth, budget deficits, rising government debts, corruption, and the global Coronavirus pandemic are contributing factors to poverty, imbalances, and economic stagnation. The history of injustices in South Africa and economic marginalisation makes it imperative to address economic challenges and inequalities using the tax policy. The wealth tax conversation has been abandoned in South Africa. Further research on the topic can make an important contribution by deepening the various aspects of wealth tax. This study explores alternative models by considering international experiences on wealth tax and adapting successful strategies to the unique context of South Africa. Wealth taxes, focusing on taxing the wealthy, are seen as a possible solution for redistributing resources to the poor. Introducing a new wealth tax carries unknown risks, particularly in terms of its potential impact on the already fragile economy that cannot afford to lose capital and investment. The lack of research on wealth tax in the South African context, as well as the limited literature on the perspective of wealthy individuals, underscores the importance of this qualitative study. The whole idea of wealth tax is that taxing those who are wealthier will provide much-needed resources for the marginalised group and be seen as a perfect tool to redistribute wealth In general theory, the wealth tax is described as a levy imposed on an individual’s net wealth, that is on the market value of all individual assets minus liabilities, this kind of tax has been ignored or not given as much attention as the other means of government revenue tax collection. Such a tax can be fraught with risks, and not all of them are known. There is fear that those affected parties may feel vulnerable and resort to tax immorality or tax evasion, which is also a great concern as it could negatively impact the economy and lead to loss of capital and investment. There is not much research on the wealth tax that focuses on the issues faced by South Africans. The aim of this study is to examine whether there will be a benefit to introducing a progressive wealth tax in the existing revenue stream, looking at possible tax relief by broadening the tax base over a period of time, evaluating the existing wealth tax, and identifying the methods that could be used to avoid the double taxation, tax evasion, and avoidance.The research is conducted using a qualitative method by analysing various literature reviews on wealth tax data, to determine the advantages and disadvantages of introducing a progressive wealth tax. The report is intended for the purpose of analysing existing wealth tax theories to see if the introduction of a progressive wealth tax would benefit South Africans. The study also contributes to ongoing political and economic debates and potentially forms part of future changes in tax policy
A research report submitted In partial fulfillment of the requirements for the degree of Masters in Bachelor of Commerce (Taxation) School of Accountancy, University of the Witwatersrand 2023
Keywords: Wealth Tax; Wealth Distribution; Inequality; Capital Gains; UCTD; SDG-8: Decent work and economic growth